Phenolic distribution in apple epidermal and outer cortex tissue by multispectral deep-UV autofluorescence cryo-imaging. (June 2019) - Vidot, Kevin; Devaux, Marie-Françoise; Alvarado, Camille; Guyot, Sylvain; Jamme, Frederic; Gaillard, Cédric; Siret, René; Lahaye, Marc
Highlights: Analysis of deep-UV cryo-microfluorescence images allowed mapping phenolic families. Apple phenolic families were mapped in epidermal and outer cortex tissue. Phenolic distribution in outer tissues differs with variety but not with storage. Abstract: Phenolic compounds in fruit are involved in responses to biotic and abiotic stresses and are responsible for organoleptic properties. To establish the distribution of these secondary metabolites at the tissue and sub-cellular scales, mapping of fluorescence in apple epidermis and outer cortex tissue in cryogenic condition was performed after deep-UV excitation at 275 nm. Douce Moën and Guillevic cider apple varieties were sampled and frozen after harvest, after 30 days at 4 °C and after 20 days at room temperature. Image analysis of fluorescence emission images acquired between 300 and 650 nm allowed the assignment of fluorescence signals to phenolic compound families based on reference molecules. Emission attributed to monomeric and/or condensed flavanol was localized in whole tissue with major fluorescence in the cuticle region. Hydroxycinnamic acids were found predominantly in the outer cortex and appeared in the cell wall. Fluorescent pigments were mostly found in the epidermis. The distribution of flavanols in the sub-cuticle and phenolic acids in the outer cortex distinguished apple varieties. Storage conditions had no impact on phenolic distribution. The proposed fluorescent imaging and analysis approach enables studies on phenolic distribution in relation to fruit development, biotic/abiotic stress resistance and quality.